Agronomic efficiency of organomineral fertilizer in onion cultivation - Oliveira, Roberta Camargos; Rosa , Hugo Franco de Novaes; Silva , Sergio Macedo; Queiroz , Angélica Araújo; Queiroz Luz , José Magno (Comunicata Scientiae, 2023)
Onions has high nutritional and nutraceutical value. In the last decade the bulbs have gained increasing relevance due their compounds linked to anti-cancer effects. The fertilization managment is relevant to this crop because the mineral’s influence beyond productivity, interfering in several aspects of quality. Organic sources despite available, adoption is still cautious and seen as an expense, rather than investment in soil quality. Therefore, the objective was to evaluate the use of organomineral fertilizer on the development and productivity of Akamaru hybrid. The experiment was carried out in Cristalina-GO, in a randomized block design, with 4 replications and 5 treatments: organomineral fertilizer (NPK) with the formula 02-20-05. The rates were adjusted to approximately the same amounts, where 3,680 kg ha-1 was considered the 100% rate, 2,944 kg ha-1 as 80%, 2,208 kg ha-1 as 60% and 1,472 kg ha-1 as 40% of the rate established. The rate of 2,300 kg ha-1 of the formulated 03-35-06 referred to 100% of the mineral source. The total yield of onion was not affected when the organomineral source was used, therefore, it is a viable source for use in onion culture. A rate reduction of up to 20% of the recommended mineral rate allows good performance (85.5 t ha-1), with 7.5 t ha-1 higher than the 60% reduction of the recommended rate.